The Five Major Factors in the Personality and Quality of Career of Teachers who are Late in Marriage: A Comparative Study Based on Gender - Moubedeen, Ahed Mohammad Khallel (Dirasat: Educational Sciences, 2022)
Objectives: The current study aimed to identify the nature of the five major factors in the personality and quality of career of teachers who are late in marriage—a comparative study of gender differences. To achieve the research objectives, the category of teachers who are late in marriage was selected from males over 35 years of age and females over 30 years of age. Methods: The study sample consisted of 190 male and female teachers, and the list of the five major personality factors prepared by Costa and Macrae (1992, Costa & Mc Crae) was used. The Career Life Scale was developed, the psychometric characteristics of the two scales were verified by honesty and consistency, and the descriptive-correlative-analytical approach was used. Results: The study’s findings showed that extroversion, harmony, conscientiousness, openness, and neuroticism were the traits teachers possessed in that order. Additionally, the quality of their career lives was found to be average, and there was a positive correlation between these traits and the quality of their careers, as well as a negative correlation between the neuroticism trait and the quality of their careers. Conclusions: The study came out with some recommendations, including the need to pay attention to the nature of the relationship between personality patterns and the quality of the careers of teachers.